The Effectiveness of Fraction Wheel Media in Improving Mathematics Learning Outcomes among Third-Grade Primary Students - Khotijah Khotijah; Masrifatin Munawwaroh; Mohammad Ryan Hidayatulloh; Halimahtus Syadiyah; Ainul Fithriyah (Information Technology and Science (ITScience), 2026)
This study aims to improve student learning outcomes in fractions through the use of the Fraction Wheel media in grade 3 at MI Thoriqul Huda Randupadangan. The research method used is Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles. The research subjects were 25 third-grade students consisting of 14 male students and 11 female students. Data collection techniques used observation of activities, learning outcome tests, and student response questionnaires. The results showed a very significant increase in learning outcomes, where the class average score increased from 52.8 in cycle I to 85.8 in cycle II. The percentage of classical learning completeness increased sharply from only 8% in cycle I to 96% in cycle II. This increase was also accompanied by a strengthening of teacher activity, which reached 96%, and student activity, which reached 87.5% at the end of the cycle. The Fraction Wheel Media proved to be effective in transforming abstract mathematical concepts into interactive concrete visualizations, thereby increasing positive responses and student learning motivation to 87,63. Thus, the use of fraction wheel media has been proven to optimally improve mathematics learning outcomes and provide an innovative and enjoyable learning solution for madrasah ibtidaiyah students.